2007
DOI: 10.1557/proc-1046-w03-08
|View full text |Cite
|
Sign up to set email alerts
|

The Use of A Multidisciplinary Project to Expand the Materials Science Curriculum

Abstract: A special interdisciplinary project course was offered in the Fall of 2006 within the Carnegie Institute of Technology at Carnegie Mellon University. The course was open to students from across the university, it drew participants from Civil and Environmental Engineering, Engineering and Public Policy, Materials Science and Engineering, Architecture, the School of Design. This multidisciplinary collection of students formed the necessary knowledge base to approach the various tasks of the project. Each student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…For example, the U.S. Green Building Council's Leadership in Energy and Environmental Design (LEED) rating system has served this purpose in capstone design courses 13,14 , as well as technical design courses 8 . Other studies have met sustainability course objectives using the LEED rating system through projects focused on sustainable energy systems 15 and collaboration of multidisciplinary students on a single project 16 . These past applications have found knowledge and student satisfaction to be improved due to the approaches taken to teach sustainability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the U.S. Green Building Council's Leadership in Energy and Environmental Design (LEED) rating system has served this purpose in capstone design courses 13,14 , as well as technical design courses 8 . Other studies have met sustainability course objectives using the LEED rating system through projects focused on sustainable energy systems 15 and collaboration of multidisciplinary students on a single project 16 . These past applications have found knowledge and student satisfaction to be improved due to the approaches taken to teach sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that in the future the module lessons will need to mention climate change concepts and adaptation and then reinforce during the Envision application. 16. Give one example of a specific action/aspect of project that could earn Envision credits.…”
mentioning
confidence: 99%